2013
DOI: 10.1002/hep.26079
|View full text |Cite
|
Sign up to set email alerts
|

Dating the origin and dispersal of hepatitis B virus infection in humans and primates

Abstract: The origin of hepatitis B virus (HBV) infection in humans and other primates remains largely unresolved. Understanding the origin of HBV is crucial because it provides a framework for studying the burden, and subsequently the evolution, of HBV pathogenicity with respect to changes in human population size and life expectancy. To investigate this controversy we examined the relationship between HBV phylogeny and genetic diversity of modern humans, investigated the timescale of global HBV dispersal, and tested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
164
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(183 citation statements)
references
References 42 publications
16
164
1
2
Order By: Relevance
“…The colonization-adaptation trade-off (CAT) model reconciles the high short-term and apparently low long-term HBV evolutionary rates reported in the literature (2,4,5,23,24). In chronic HBV, limited host immunity against HBV at an early stage (the immune tolerance or noninflammatory phase) (8,11) might favor viruses with a high replication ability (represented by the blank area in the upper circles in Fig.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The colonization-adaptation trade-off (CAT) model reconciles the high short-term and apparently low long-term HBV evolutionary rates reported in the literature (2,4,5,23,24). In chronic HBV, limited host immunity against HBV at an early stage (the immune tolerance or noninflammatory phase) (8,11) might favor viruses with a high replication ability (represented by the blank area in the upper circles in Fig.…”
Section: Discussionsupporting
confidence: 54%
“…The time-dependent HBV substitution rate may shed light on the evolutionary origin of HBV, which is still controversial, because the substitution rates required for HBV/human codivergence are an order of magnitude lower than those estimated based on extant sequences (3,4,23,25,26). Figure 2A We applied these equations to test if the divergence of the HBV-F/H genotypes from American Indians corresponded to their first colonization of the Americas.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that WMHBV, like human HBV, uses Tupaia NTCP as a cellular receptor for entry into PTHs. Given that among all of the primate HBV family members, WMHBV is phylogenetically the most distant from human HBV (12,28), and both WMHBV and HBV utilize Tupaia NTCP to infect PTHs, it is conceivable that NTCP likely serves as a common cellular receptor for the entry of all known primate hepadnaviruses into host cells.…”
Section: Fig 4 Inhibition Of Wmhbv Infection In Pths By Tsntcp-bindinmentioning
confidence: 99%
“…The current paper reports the demographic, epidemiological, and clinical characteristics of 170 HBsAg-positive 2 Hepat Mon. 2017; 17(8):e13260.…”
Section: Study Populationmentioning
confidence: 99%